The poetry of minor characters and everyday life in the Sĕrat Cĕnthini - Day, Tony (Wacana, Journal of the Humanities of Indonesia, 2021)
The 722 cantos and 247,766 lines of poetry in the Sĕrat Cĕnthini, composed in Surakarta by Ki Ng. Ronggasutrasna, R.Ng. Yasadipura II, and Ki Ng. Sastradipura under the direction of the Crown Prince of Surakarta (later Pakubuwana V, r.1820-1823) in 1815 during the British occupation of Java (1811- 1816), are arguably the greatest expression of literary art ever written in Javanese. The earliest version of the Sĕrat Cĕnthini comes from Cirebon at the beginning of the seventeenth century. When the poem reached Surakarta in the late eighteenth to early nineteenth century, court poets rewrote it, greatly expanding the number of episodes and characters, as well as the kinds of information and literary style to be found in the text. My interest in the excerpt I have translated from Canto 364 focuses on two aspects of this process of literary revision: characterization and the representation of everyday life.